2022
DOI: 10.3389/fimmu.2022.996897
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome-metabolome analysis reveals alterations in the composition and metabolism of caecal microbiota and metabolites with dietary Enteromorpha polysaccharide and Yeast glycoprotein in chickens

Abstract: The intestinal microbiome is responsible for the fermentation of complex carbohydrates and orchestrates the immune system through gut microbiota-derived metabolites. In our previous study, we reported that supplementation of Enteromorpha polysaccharide (EP) and yeast glycoprotein (YG) in combination synergistically improved antioxidant activities, serum lipid profile, and fatty acid metabolism in chicken. However, the mechanism of action of these polysaccharides remains elusive. The present study used an integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
(55 reference statements)
2
4
0
Order By: Relevance
“…According to Lin et al [ 113 ], quercetin supplementation increased the numbers of Bacteroides and other bacteria. Wassie et al [ 114 ] found that supplementation with Enteromorpha polysaccharide increased the abundance of the Bacteroidetes phylum and Bacteroides genus, and the increased cecal levels of acetic, butyric, and propionic acids suggested that Enteromorpha polysaccharides enhanced the ability of the microbiota to induce SCFAs, which is in line with our results. In this study, dietary TCE treatments increased the Bacteroidaceae content and Bacteroides abundance.…”
Section: Discussionsupporting
confidence: 92%
“…According to Lin et al [ 113 ], quercetin supplementation increased the numbers of Bacteroides and other bacteria. Wassie et al [ 114 ] found that supplementation with Enteromorpha polysaccharide increased the abundance of the Bacteroidetes phylum and Bacteroides genus, and the increased cecal levels of acetic, butyric, and propionic acids suggested that Enteromorpha polysaccharides enhanced the ability of the microbiota to induce SCFAs, which is in line with our results. In this study, dietary TCE treatments increased the Bacteroidaceae content and Bacteroides abundance.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in 5-hydroxyindoleacetic acid promotes tryptophan metabolism, which is also beneficial to maintain intestinal homeostasis [ 50 ]. Similar to our finding, KRS was shown to have a beneficial effect on enhancing intestinal metabolism by increasing the metabolism of glycine, serine, and threonine in the intestine [ 51 ]. In addition, KRS promoted glutathione metabolism and lipid metabolism in the intestine, which may explain the enhanced activity of intestine antioxidant enzymes and decreased serum lipids.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the researchers observed an increase in dopamine concentration specifically in the EP+YG-treated group. This finding suggests that EP + YG modulates metabolites associated with neurotransmitters and immune responses, indicating a potential role in enhancing both neurological and immunological functions ( 47 ).…”
Section: Gut Microbiota and Host Immunitymentioning
confidence: 99%